All-polyethylene versus metal-backed posterior stabilized total knee arthroplasty: similar 2-year results of a randomized radiostereometric analysis study - Hasan, Shaho; Marang-van de Mheen, Perla J; Kaptein, Bart L; Nelissen, Rob G H H; Toksvig-Larsen, Sören (Acta Orthopaedica, 2019)
Background and purpose — The all-polyethylene tibial (APT) component, introduced in the early 1970s, was surpassed by metal-backed tibial (MBT) trays as the first choice for total knee arthroplasty (TKA). With improved polyethylene, the modern APT components can reduce costs, and have shown equivalent results in survivorship and early migration of the cruciate-retaining and cruciate-stabilizing designs. This study compares the 2-year migration of a similarly designed APT-posterior stabilized (PS) and a MBT-PS TKA, using radiostereometric analysis (RSA). Patients and methods — 60 patients were randomized to receive either an APT Triathlon PS or an MBT Triathlon PS TKA (Stryker, NJ, USA). Migration measured by RSA and clinical scores were evaluated at baseline and at 3, 12, and 24 months postoperatively. Repeated measurements were analyzed with a linear mixed model and generalized estimating equations. Results — The mean maximum total point movement (MTPM) at 3, 12, and 24 months was 0.41 mm (95% CI 0.33–0.50), 0.57 mm (0.44–0.70), and 0.56 mm (0.42–0.69) respectively in the MBT group and 0.46 mm (0.36–0.57), 0.61 mm (0.49–0.73), and 0.64 mm (0.50–0.77) in the APT group. 2 MBT and 1 APT implant were considered unstable at the 2-year follow-up. The KSS Knee score and KSS Function across 3, 12, and 24 months were comparable in both groups. Interpretation — For an APT-PS designed component, MTPM measured with RSA is comparable to the MBT-PS component after 2 years of follow-up. No differences in complications or clinical outcomes were found.